Covalent-supramolecular hybrid polymers as muscle-inspired anisotropic actuators - Stacey M. Chin (Nature Portfolio, 2018)
Skeletal muscles are impressive as they can achieve reversible, macroscopic, anisotropic motion in soft materials. Here the authors show a bottom-up design of macroscopic hydrogel tubes containing supramolecular nanofibers that can undergo anisotropic actuation by thermal stimuli.